Activated Hippo/Yes-Associated Protein Pathway Promotes Cell Proliferation and Anti-apoptosis in Endometrial Stromal Cells of Endometriosis - Song, Yong (J Clin Endocrinol Metab, 2016)
CONTEXT: The imbalance in cell proliferation and apoptosis is considered an important role in the pathogenesis of endometriosis, but the exact mechanisms remains unclear. A newly established signaling pathway–Hippo/Yes-associated protein (YAP) pathway plays a critical role in the proliferation and apoptosis processes. However, studies focusing on Hippo/YAP pathway and endometriosis are lacking. OBJECTIVE: The objective was to explore the function of the Hippo/YAP pathway in endometriosis. SETTING AND DESIGN: The expression of YAP was first investigated in endometrium of women with or without endometriosis. The role of YAP in cell proliferation and apoptosis is identified by transfection of endometrial stromal cells (ESCs) in vitro, subsequent Verteporfin treatments in eutopic ESCs in vitro, and endometriosis animal model of nude mice in vivo. RESULTS: Our results revealed that increased expression of YAP and decreased expression of p-YAP in ectopic and eutopic endometrium compared with normal endometrium. YAP knockdown in eutopic ESCs decreased cell proliferation and enhanced cell apoptosis companied with decreased expression of TEAD1, CTGF, and B-cell lymphoma/leukemia (BCL)-2; whereas overexpression of YAP resulted in increased proliferation and decreased apoptosis of normal ESCs with increased expression of TEAD1, CTGF, and BCL-2. By chromatin immunoprecipitation qPCR CTGF and BCL-2 were identified as directly downstream target genes of YAP-TEAD1 active complex. Eutopic ESCs treated with Verteporfin revealed decreased proliferation and enhanced apoptosis whereas in endometriosis animal models of nude mice treated with Verteporfin, the size of endometriotic lesions was significantly reduced. CONCLUSIONS: Our study suggests that the Hippo/YAP-signaling pathway plays a critical role in the pathogenesis of endometriosis and should present a novel therapeutic method against endometriosis.